Syria's Sunnis and the Regime's Resilience - Zambelis, Chris
Syria s calamitous civil war is now in its fourth year. Amid the rising body count and destruction, there is little clarity about the viability of Syrian President Bashar al-Assad s Ba athist regime even as the numerous violent insurgent organizations that seek to topple his administration receive ample attention. Social media has enabled observers to scrutinize the armed opposition in almost real-time via their public declarations, battlefield operations, and propaganda.
Keywords: Islamismo; Resiliencia; Siria